Molecular mechanisms of platelet aggregation - Bakunovich, Andrei V.; Bulanova, Klavdiya Y.; Lobanok, Leonid M. (Journal of the Belarusian State University. Ecology, 2018)
The article deals with the processes occurring in platelets during their activation caused by a multitude of agonists affecting a number of structural and functional molecules of the membrane surface, as well as specific receptors that activate different signaling pathways. Some of them ensure the maintenance of hemostasis in case of vascular integrity dis-orders, others - trigger the synthesis of biologically active molecules. Accordingly, most attention is paid to the molecular mechanisms of the haemostatic reaction: the processes of platelet recognition of the damaged wall of the blood vessel, adhesion to the endothelium, their subsequent activation and aggregation; role of glycoprotein complex, collagen in ad-hesion and platelet aggregation; the predominant participation of the most important signaling pathways and the leading role of secondary messengers in activation-deactivation of platelets. The article also presents data of various enzymatic processes in platelets that determine the synthesis of different types of eicosanoids.
Keywords: platelets; platelet adhesion and aggregation; calcium ions; purinoreceptors; platelet activation; cAMP; cGMP; glycoprotein complex